Beyond ghost games: The value of avoiding COVID-19 with masking and social distancing in U.S. professional sports." - Humphreys, B.; Wagner, G. A.; Whitehead, J. C.; Wicker, P. (University of Reading, 2020)
The thirty third Reading Online Sport Economics Seminar (ROSES) by John Whitehead of Appalachian State University, presenting "Beyond ghost games: The value of attendance with masking and social distancing in U.S. professional sports".